ABSORPTION OF EUROPEAN FUNDS, PRIORITY OBJECTIVE FOR LOCAL COMMUNITIES DEVELOPMENT - CONSTANTIN BRAGARU (Challenges of the Knowledge Society)
This paper analyzes the absorption capacity of structural funds in Romania in the programming period 2007- 2013 and its impact on the development of local communities from the administrative point of view. The paper also focuses on the need to invest in institutional capacity and efficiency of public administrations using the Operational Programme for Administrative Capacity Development 2007-2013 which is a part of ESF funds that have as general objective to contribute to the creation of a more efficient and effective public administration for the socio-economic benefit of local communities. Finally, the study reveals the problems and challenges related to local administration and its limited capacity to absorb european funds wich is a sensitive issue, especially because 2011 represents the fifth year of EU assistance for Romania to reach the stage of development of other member states.